THE EFFECT OF PROFIBILITY AND LEVERAGE ON TAX AVOIDANCE (Study of Agricultural Sector Companies in the Plantation Sub-Sector Listed on the Indonesia Stock Exchange) - Dick Wolters Marbun; Mila Susanti (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This study aim was to see whether profitability and leverage had an impact toward tax avoidance. The data used in this study were secondary data taken from the financial statements of agricultural sector plantation companies listed on the Indonesia Stock Exchange in 2015-2018. This study used descriptive analysis, linear regression and significant test. The results of this study indicated that profitability in agricultural sector plantation companies had a significant effect on tax avoidance. Likewise, leverage had a significant effect on tax avoidance, but the simultaneous test measurement of profitability and leverage on tax avoidance did not have a significant effect on tax avoidance.